An Exploration of 11th Grade Students’ Intrinsic Motivation in Learning English in SMKN 1 Bukittinggi (Jurnal Sosial Humaniora dan Pendidikan, 2025)
This study examines the level and factors influencing students’ intrinsic motivation in learning English at SMKN 1 Bukittinggi, specifically among 11th-grade students who struggled to meet academic standards and showed low interest in independent learning. An explanatory sequential mixed-method approach was employed, using questionnaires and interviews. The instruments were tested for construct validity and test-retest reliability. Results showed that the majority of students had moderate intrinsic motivation, with 12% displaying high motivation, 79% moderate, and 9% low. Key factors identified were strong character traits such as integrity and responsibility, self-awareness, mental resilience, and effective coping strategies for overcoming failures. These findings suggest that students’ intrinsic motivation is influenced by personal qualities and their ability to handle challenges, which play a crucial role in their engagement and persistence in learning English as a foreign language.